The role of tumour volume as a prognostic factor in non-small cell lung cancer (NSCLC) patients treated with definitive radiotherapy. Issue 3 (15th February 2019) - Joyce, R.; O'Boyle, G.; McDermott, R. L.; Small, C.
Abstract: Background: It has been shown that patients with a greater tumour volume have poorer outcomes following definitive radiotherapy but its exact role remains unclear. The purpose of this study is to investigate the role of tumour volume as a prognostic indicator in non-small cell lung cancer (NSCLC) patients treated with definitive radiotherapy in a single institution over 10 years. Methods: In total, 167 patients with NSCLC treated by definitive (chemo)radiotherapy were retrospectively reviewed between 2006 and 2015. Patient demographics, disease characteristics and tumour volume parameters were collected. Univariate analyses were carried out using Kaplan–Meier survival curves to assess the association of potential prognostic factors with the primary endpoints of overall survival (OS) rates and locoregional recurrence rates. Multivariate analyses were carried out using a Cox regression method. Results: The median total tumour volume (TTV), defined as the gross tumour volume plus the volume of involved nodes, was 103 cm 3 . Patients were divided into small and large tumour groups based on this median. OS rates at 1, 3 and 5 years for smaller volumes were 69%, 24% and 13% and for larger volumes 48%, 14% and 8%, respectively. On univariate survival analyses larger TTV was significantly associated with poorer OS ( p = 0·019). The concurrent use of chemotherapy significantly improved survival ( p = 0·026). Nodal involvement ( p = 0·03) and Eastern Cooperative Oncology Group performance status ( p < 0·001) were also significant independent prognostic factors of OS. On multivariate analysis TTV was strongly predictive of survival ( p = 0·03; hazard ratio 1·702, 95% confidence interval 1·198–2·415). There was no association between nodal volume, tumour stages, overall stage, age, histology and radiation dose with any of the primary endpoints. Conclusion: TTV is a significant prognostic factor in patients with advanced NSCLC treated by radical radiotherapy. In this cohort of patients TTV is more reliable at predicting survival than T stage and overall stage.